A Simulation Model for Financial Programming. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper describes a simulation model that can serve as a basis for a developing country growth-oriented adjustment program. The model has been designed to provide explicit links between fiscal, monetary and exchange rate policies and major macroeconomic variables. While the model is applied to and solved for the case of Turkey, its simplicity and flexibility make it sufficiently general to be applicable to a wide range of countries. The model integrates demand-determined output with a supply side that responds to policies which affect investment and it allows the relative shares of domestic and foreign factors of production to be determined by their relative prices. The model is solved using Lotus 1-2-3, software that is familiar to Fund economists and which allows the user to quickly evaluate alternative assumptions and policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet